Comprehensive next-generation sequencing reveals double primary colorectal carcinoma missed by diagnostic imaging: A case report - Qu, Yan-Jun; Zhang, Qian-Shi; Wang, Bo; Zhang, Feng; Pan, Evenki; Zhao, Chun-Yan; Liu, Si-Ye; Fang, Li-Ping (World journal of gastrointestinal oncology, 2023)
Minimally invasive surgery is increasingly indicated in the management of malignant disease. Although oesophagectomy is a difficult operation, with a long learning curve, there is actually a shift towards the laparoscopic/thoracoscopic/ robotic approach, due to the advantages of visualization, surgeon comfort (robotic surgery) and the possibility of the whole team to see the operation as well as and the operating surgeon. Although currently there are still many controversial topics, about the surgical treatment of patients with gastro-oesophageal junction (GOJ) adenocarcinoma, such as the type of open or minimally invasive surgical approach, the type of oesophago-gastric resection, the type of lymph node dissection and others, the minimally invasive approach has proven to be a way to reduce postoperative complications of resection, especially by decreasing pulmonary complications. The implementation of new technologies allowed the widening of the range of indications for this type of surgical approach. The short-term and long-term results, as well as the benefits for the patient - reduced surgical trauma, quick and easy recovery - offer this type of surgical treatment the premises for future development. This article reviews the updates and perspectives on the minimally invasive approach for GOJ adenocarcinoma.